Exploring exit characteristics among czech female angel investors: A case study approach - Vejmělková, Lada (Vysoká škola Sting, 2024)
This article presents research findings on the identification of key exit characteristics of female business angels in the Czech Republic. The research is qualitative and based on case studies derived from semi-structured interviews with three female business angels. The primary data processing tool is content analysis of qualitative data, supported by quantification. The data included in the resulting data matrix are subjected to frequency analysis. The findings suggest that the main form of exit for female business angels is through trade sales. The share held by a female business angel is sold to a corporate investor, founders, or a venture capital fund. Furthermore, the research findings indicate that exits are the result of an opportunistic approach to planning the exit from the investee firm. Overall, it is concluded that a thorough grasp of these exit characteristics might improve the return on female business angel investments made in the Czech Republic, providing insightful information to both investors and policy makers and increased academic interest in this area.

This article presents research findings on the identification of key exit characteristics of female business angels in the Czech Republic. The research is qualitative and based on case studies derived from semi-structured interviews with three female business angels. The primary data processing tool is content analysis of qualitative data, supported by quantification. The data included in the resulting data matrix are subjected to frequency analysis. The findings suggest that the main form of exit for female business angels is through trade sales. The share held by a female business angel is sold to a corporate investor, founders, or a venture capital fund. Furthermore, the research findings indicate that exits are the result of an opportunistic approach to planning the exit from the investee firm. Overall, it is concluded that a thorough grasp of these exit characteristics might improve the return on female business angel investments made in the Czech Republic, providing insightful information to both investors and policy makers and increased academic interest in this area.
Exploring exit characteristics among czech female angel investors: A case study approach
Keywords: venture capital; informal venture capital; business angels; female business angels; characteristics; exit; exit strategy; Czech Republic; venture capital; informal venture capital; business angels; female business angels; characteristics; exit; exit strategy; Czech Republic